Economic Efficiency of Table Grape Production in Waterberg and Sekhukhune Districts, Limpopo Province, South Africa - Maponya, Naume; Oluwatayo, Isaac (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2020)
Table grape production plays an important role in the economy of many countries in Africa. It serves as a source of income for the people who are engaged in its production and being one of the enterprises that is labour-intensive, thereby providing employment for more people. The main purpose of this study was to analyse the economic efficiency of table grape production in Waterberg and Sekhukhune Districts of Limpopo province, South Africa. The study used primary data collected through administration of structured questionnaires on a sample of 12 farmers by employing a snowball sampling method. Analytical tools employed include descriptive statistics (such as tables and frequencies), Stochastic Frontier Model and Technical Inefficiency Model. Results from data analysis revealed that in terms of efficiency, farming experience (p